TYPE OF ERROR IN COMPLETING MATHEMATICAL PROBLEM BASED ON NEWMAN"™S ERROR ANALYSIS (NEA) AND POLYA THEORY - Winarso, Widodo; Wahid, Sirojudin; Rizkiah, Rizkiah (Jurnal Pendidikan Matematika dan IPA, 2022)
This study disscusses student"™s errors in completing mathematical problems based on Newman"™s Errror Analysis and Polya Theory. The study uses a qualitative descriptive approach. The subject of this study are 78 students of Madrasah Aliyah Negeri (MAN) 2 Cirebon. The study uses tests and interviews as data collection techniques. Students take a test to determine their mathematical ability, and the test uses sequence and series as subjects. There are 3 phases in collecting data: data reduction, data presentation, and conclusion. Outline of Error analysis is created using five types of student mathematical error of Newman's Error Analysis and four types of student mathematical error of Polya Theory. The study results based on Newman's Error Analysis are errors reading by 1%, error understanding by 0%, error transforms by 3%, error processing ability by 5%, and error encoding by 7%. As the result of the study based Polya theory, errors when understanding the problem by 31%, errors when devising a plan by 11%, errors when carrying out the plan by 9%, and errors when Looking back by 33%. The result of the interview shows that the error occurs when students don"™t do calculations carefully, don"™t learn the formula, and cannot distinguish between sequence and series. Students also have a lack of understanding when completing the problem about compound interest.